Gait speed after mild stroke/transient ischemic attack was associated with long‐term adverse outcomes: A cohort study - Ning Li; Jia Zhang; Yang Du; Jing Li; Anxin Wang; Xingquan Zhao (Annals of Clinical and Translational Neurology)
Abstract Objective The association between gait speed and adverse outcomes after stroke has not been fully illustrated. This study aimed to explore the association of gait speed on long‐term outcomes in minor stroke or transient ischemic attack (TIA). Methods We performed a longitudinal study with acute minor stroke or TIA based on a subgroup of the Third China National Stroke Registry data. The gait speed was evaluated using a 10‐meter walking test at discharge and 3 months after the stroke onset. The primary outcomes were poor functional outcomes at 1 year, defined by a modified Rankin Score (mRS) of 2–6. Additional outcomes included all‐cause death, ambulate dependency (mRS score 4–6), cognitive impairment (Montreal Cognitive Assessment <26), stroke recurrence, and composite vascular events. Results The study sample included a total of 1542 stroke patients with a median age of 60 (53–68). At 1‐year follow‐up, 140 (9.20%) patients experienced poor functional outcomes. Faster gait speed at discharge was associated with lower incidence of poor functional outcome (OR = 0.89; 95% CI, 0.84–0.94), cognitive impairment (OR = 0.93; 95% CI, 0.89–0.96), ischemic stroke recurrence (HR = 0.92; 95% CI, 0.87–0.98), and composite vascular events (HR =0.94; 95% CI, 0.89–0.99) at 1 year. Faster gait speed at 3 months was associated with lower incidence of poor functional outcome (OR = 0.90; 95% CI, 0.85–0.95), ambulate dependency (OR = 0.86; 95% CI, 0.77–0.97), and cognitive impairment (OR = 0.92; 95% CI, 0.88–0.95) at 1 year. Interpretation Our findings indicated that slow gait speed after minor stroke or TIA may be an independent predictor for long‐term poor outcomes. Gait speed may be considered as a vital sign during follow‐up in post‐stroke patients.